Mixed methods systematic review on effectiveness and experiences of the Incredible Years Teacher Classroom Management programme - Nye, E; Melendez-Torres, G; Gardner, F (Wiley, 2018)
Children's early problematic behaviour correlates with later deviant behaviour. The Incredible Years Teacher Classroom Management (IY TCM) programme trains teachers in proactive strategies to disrupt patterns of negative child behaviour. This mixed methods systematic review applies multilevel meta‐analysis and qualitative meta‐synthesis to answer: What is known about the effectiveness of IY TCM, and how do people experience the programme and its effects? We included RCTs comparing IY TCM against treatment‐as‐usual/wait‐list controls and interview/focus group studies with stakeholders. We pooled effect sizes using multilevel meta‐analysis and applied grounded theory analysis to qualitative data. We used framework analysis and integrative grids for cross‐synthesis. Nine studies from England, Ireland, Jamaica, the United States and Wales were included. IY TCM significantly reduced teachers’ use of negative classroom management strategies and reduced conduct problems among high‐risk children. No significant effects were found for improving child prosocial behaviours. Qualitative findings illuminated iterative learning processes between the individual and group and identified a wider range of perceived benefits than was measured in trials. Cross‐synthesis demonstrates both harmonious overlap and gaps from differing research priorities. IY TCM presents an opportunity to lessen violence in schools, leading to improved learning environments for all. It reduced teachers’ negative classroom management practices and high‐risk children's aggressive/non‐compliant behaviours. Experiential data mirrors these findings and expands upon them with a wide range of perceived benefits, demonstrating IY TCM is acceptable and enjoyable. Future quantitative research should seek to test the processes produced in the qualitative meta‐synthesis, to better understand mechanisms of change.